Left Posterior Approach to the Superior Mesenteric Vascular Pedicle in Pancreaticoduodenectomy for Cancer of the Pancreatic Head - Kurosaki, Isao; Minagawa, Masahiro; Takano, Kabuto; Takizawa, Kazuyasu; Hatakeyama, Katsuyoshi (JOP. Journal of the Pancreas, 2011)
Context Dissection of the superior mesenteric artery is the most important part of a pancreaticoduodenectomy for pancreatic cancer. Since 2005, we have used the left posterior approach for superior mesenteric vascular pedicle dissection, in which the superior mesenteric artery and the superior mesenteric vein are dissected first in a clockwise fashion. Objective This article presents the technique of a left posterior approach and the clinical outcome. Patients Forty patients underwent a left posterior approach and were compared to 35 patients treated with a conventional dissection. Main outcome measures The differences in surgical technique between the left posterior approach and the conventional method were described, and the short- and long-term surgical results compared patients who underwent the left posterior approach to those who were treated with the conventional method. Intervention The superior mesenteric vascular pedicle was first dissected from the left lateral border of the superior mesenteric artery. The superior mesenteric vein was also dissected from the left side. Then, the uncinate process and perivascular soft tissue were separated en bloc from the vasculature. Results No life-threatening complications occurred after the pancreaticoduodenectomies using a left posterior approach. Diarrhea requiring the administration of antidiarrheal agents occurred in 65% of patients; however, planned adjuvant chemotherapy was completed in all patients who did not have an early tumor recurrence. Survival rate was 52.8% at 3 years after surgery. Conclusion After a pancreaticoduodenectomy with a left posterior approach, most patients had various degrees of diarrhea, but the adjuvant chemotherapy was able to be continued with close monitoring. The left posterior approach facilitates understanding of the topographic anatomy in the superior mesenteric vascular pedicle. Image: Technical illustration of the transverse plane (detail).